Evaluation of education in the contemporary world from a perspective of holistic approach - SAHINOGLU Seyfullah (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The main purpose of education is generally expressed as raising strong, visionary and qualified generations who will transfer the social and cultural heritage from generation to generation. In today's world, where global problems have the same effect even in the farthest corners of the world, establishing and maintaining a quality education system has become a phenomenon that almost all societies dream of. In multi-religious and multi-cultural societies with individuals who belong to different religions, languages, sects, races, genders and ethnic origins having different beliefs, morals and thoughts, it is an extremely important issue to be able to form and develop a sustainable common life skill. Nowadays, from an educational perspective this issue is accepted as "an indispensable situation and an indisputable fact". There is no doubt that the emphasize on the holistic approach, which has inspired so many effective and popular education systems around the world in terms of the scientific competence, gives a special meaning to the original value of the subject. The holistic approach according to scope, adequacy and conformity criteria reveals the basic universal principles of education thanks to its innovative tendencies and attitudes, and thus makes significant contributions to the realization of the qualified education.